2009
DOI: 10.1063/1.3226674
|View full text |Cite
|
Sign up to set email alerts
|

Single-shot ultrafast electron diffraction with a laser-accelerated sub-MeV electron pulse

Abstract: We have demonstrated single-shot measurement of electron diffraction patterns for a single-crystal gold foil using 340 keV electron pulses accelerated by intense femtosecond laser pulses with an intensity of 2×1018 W/cm2. The measured electron beam profile is faithfully reproduced by the numerical simulation of the electron trajectory, providing evidence that the electron pulse spontaneously expands in time owing to the velocity spread produced in the acceleration process, but is not distorted in an irreversib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 26 publications
0
39
0
Order By: Relevance
“…In Ref. 20, single shot diffraction patterns have been recorded from a single crystal. As our electron source provides a similar number of electrons/shot, we believe that extension to single shot data could be performed by (i) using a single crystal sample (ii) increasing the effective quantum efficiency (QE) of our detection system.…”
Section: -mentioning
confidence: 99%
See 1 more Smart Citation
“…In Ref. 20, single shot diffraction patterns have been recorded from a single crystal. As our electron source provides a similar number of electrons/shot, we believe that extension to single shot data could be performed by (i) using a single crystal sample (ii) increasing the effective quantum efficiency (QE) of our detection system.…”
Section: -mentioning
confidence: 99%
“…For UED applications, electron bunches from plasmas should be manipulated, and the linear chirp can be compensated using existing magnetic optics technology. 19 Tokita et al 20 have recently performed high-intensity laser-solid interaction experiment and demonstrated that electrons originating from the back of a solid target can be used to obtain single shot and high quality diffraction images. A temporal resolution of 500 fs was obtained after compensation of the linear chirp 21 so that the temporal resolution might be due to the intrinsic bunch duration given by the interaction mechanism: electron recirculation in the target might elongate the bunch duration.…”
mentioning
confidence: 99%
“…The emittance required for single-shot imaging depends on the size of the object being imaged: larger object sizes or crystal periods require lower emittance to generate useful coherent diffraction patterns. Ultrafast single-shot electron diffraction has been achieved from large single crystal and polycrystalline samples using a variety of photocathode based sources [13][14][15][16][17] , but insufficient source brightness has prevented demonstration for micro or nanocrystals, or single molecules.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been ob served that laser-accelerated ions are generated at distances up to a few millimeters away from the laser-irradiated region [12], and that the maximum proton energy is increased by using disk targets with a diameter of a few millimeters [13], Therefore, it is essential to observe and understand the dynamics of fast electrons, and the electromagnetic fields that they induce, over a large region (on the order of several millimeters) outside the laser-irradiated region for various materials. This could aid the development of efficient laser-induced plasma radiation sources for many attractive applications, including fast ignition for inertial confinement fusion [14,15], ultrafast electron diffraction measurements [16,17], time-resolved x-ray probes [18,19], laser-driven nuclear physics [20], and tumor therapy using ion beams [21 ].…”
Section: Introductionmentioning
confidence: 99%